2011
DOI: 10.1371/journal.pone.0018045
|View full text |Cite
|
Sign up to set email alerts
|

Further Improvements of the P. falciparum Humanized Mouse Model

Abstract: BackgroundIt has been shown previously that it is possible to obtain growth of Plasmodium falciparum in human erythrocytes grafted in mice lacking adaptive immune responses by controlling, to a certain extent, innate defences with liposomes containing clodronate (clo-lip). However, the reproducibility of those models is limited, with only a proportion of animals supporting longstanding parasitemia, due to strong inflammation induced by P. falciparum. Optimisation of the model is much needed for the study of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 50 publications
8
66
0
Order By: Relevance
“…Because P. falciparum cannot infect rodent erythrocytes and rodent malaria parasites lack many Ags of P. falciparum, including CyRPA, nonhuman primates or SCID-mice engrafted with human erythrocytes are the only in vivo models available to study growth inhibitory effects of CyRPA-specific Abs. It was previously shown that the P. falciparum model in NOD-SCID mice genetically deficient in IL-2R g-chain (NODscid IL2Rg null ) engrafted with human erythrocytes is a reliable test system for drug evaluation in vivo (65,80). Also in our hands, parasite growth in infected NOD-scid IL2Rg null mice was very consistent and reproducible.…”
Section: Discussionsupporting
confidence: 65%
“…Because P. falciparum cannot infect rodent erythrocytes and rodent malaria parasites lack many Ags of P. falciparum, including CyRPA, nonhuman primates or SCID-mice engrafted with human erythrocytes are the only in vivo models available to study growth inhibitory effects of CyRPA-specific Abs. It was previously shown that the P. falciparum model in NOD-SCID mice genetically deficient in IL-2R g-chain (NODscid IL2Rg null ) engrafted with human erythrocytes is a reliable test system for drug evaluation in vivo (65,80). Also in our hands, parasite growth in infected NOD-scid IL2Rg null mice was very consistent and reproducible.…”
Section: Discussionsupporting
confidence: 65%
“…Immunocompromised mice into which hurbc are continuously injected are able to support P. falciparum blood-stage infections, but the drawbacks are that the mice either have to be infected with adapted strains of P. falciparum (36) or continuously treated with clodronate liposomes to deplete macrophages (37). If the FRG NOD huHep mouse was also used for hurbc reconstitution, the clodronate depletion of the resident macrophages in the liver, the Kupffer cells, might have an effect on liver infection by sporozoites.…”
Section: Quantification Of P Falciparum Ls Burden In the Frg Huhep Mmentioning
confidence: 99%
“…A further application of this technology is to humanize mice with such cells (Arnold et al, 2011;Legrand et al, 2009) in order to study many aspects of host-parasite relation in vivo in an unprecedented way. The generation of mice with gene defects that prevent formation of T and B cells (scid or rag mutations) and natural killer cells (through IL-2 receptor γ chain deficiency) resulted in models that sustain meaningful numbers of human blood cells (Ito et al, 2002;Traggiai et al, 2004), and these models are continuously being improved (Brehm et al, 2012;Strowig and Flavell, 2012).…”
Section: What Are Stem Cells and How Can They Be Generated In Vitro?mentioning
confidence: 99%